2015
DOI: 10.1155/2015/456305
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms of Herbal Therapies for Inhibiting HMGB1 Secretion or Action

Abstract: High mobility group box 1 (HMGB1) is an evolutionarily conserved protein and is constitutively expressed in virtually all types of cells. In response to microbial infections, HMGB1 is secreted from activated immune cells to orchestrate rigorous inflammatory responses. Here we review the distinct mechanisms by which several herbal components inhibit HMGB1 action or secretion, such as by modulating inflammasome activation, autophagic degradation, or endocytic uptake. In light of the reciprocal interactions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 133 publications
(154 reference statements)
0
35
0
Order By: Relevance
“…However, it may be modified by acetylation and translocate into the cytoplasm and then released from activated cells [34]. Thus, deacetylation of HMGB1 by SIRT1 prevents its translocation from nucleus to cytoplasm and subsequent release [35].…”
Section: Resultsmentioning
confidence: 99%
“…However, it may be modified by acetylation and translocate into the cytoplasm and then released from activated cells [34]. Thus, deacetylation of HMGB1 by SIRT1 prevents its translocation from nucleus to cytoplasm and subsequent release [35].…”
Section: Resultsmentioning
confidence: 99%
“…17 Preclinical animal studies of inflammatory diseases such as sepsis revealed that both GLY and CBX inhibit expression, extracellular secretion and cytokine activity of HMGB1 and other proinflammatory cytokines. 16,38 However, the underlying mechanisms of GLY or CBX regulation of the extracellular cytokine activity of HMGB1 in inflammatory diseases remained poorly understood. Recent studies, however, using an endotoxemic mouse model and LPS-treated RAW 264.7 cells shed some light on this issue, showing that GLY treatment induced heme oxygenase 1 expression via a p38MAPK/Nrf2 pathway, inhibiting HMGB1 extracellular secretion and hence its extracellular cytokine activity.…”
Section: Discussionmentioning
confidence: 99%
“…1618 Glycyrrhizin is a glycoconjugated triterpene extracted from licorice root ( Glycyrrhiza glabra ). It possesses numerous pharmacologic effects 19 and has been shown effective in animal models of sepsis, 20 colitis, 21 lung, 22 and brain 23 injury.…”
mentioning
confidence: 99%
“…Several molecular mechanisms by which herbal components effectively block HMGB1 release are postulated [18]. Glycyrrhizin inhibits LPS-triggered HMGB1 release through binding to HMGB1 in order to induce conformational changes that prevent DNA binding [18, 19].…”
Section: Introductionmentioning
confidence: 99%